Five-year treatment outcomes with three brands of implants supporting mandibular overdentures - (:unkn) unknown (My University, 2011)
Purpose: The purpose of this study was to evaluate clinical outcomes, posttreatment care, and patient satisfaction with overdenture treatment in the severely resorbed mandible. Materials and Methods: Two implants were inserted in the intraforaminal region of 36 edentulous patients. Seventy-two implants were placed: 24 ITI (Institut Straumann), 24 SwissPlus (Zimmer Dental), and 24 Astra (Astra Tech). Implants were not loaded until osseointegration was complete. Following osseointegration and insertion of the prosthesis, the implants were evaluated by clinical and radiographic parameters. Clinical parameters, including Plaque Index, Sulcus Bleeding Index, peri-implant probing depth (PD), and marginal bone loss (MBL), were recorded, and any biologic and mechanical complications at baseline and recall evaluations were noted. Patient satisfaction with mastication, phonetics, retention, oral hygiene, and esthetics was also evaluated by means of a questionnaire. The results were analyzed statistically. Results: The cumulative implant survival rate after 5 years of loading was 100%. There were significant differences in mean PD values between the three implant groups at baseline and recall evaluations. Mean PD values for the Astra group were significantly higher than those for the ITI and SwissPlus groups. Although the mean MBL was within clinically acceptable levels for all groups, there were significant differences among the three groups for MBL scores between baseline and 5 years. The mean MBL for the ITI group was significantly lower than the MBL values seen for the Astra and SwissPlus groups. Over the 60-month evaluation period, the most common prosthetic complications were mandibular denture fracture and dislodgement of the female attachment. Conclusions: Mandibular implant overdenture treatment is a successful treatment modality for the severely resorbed mandible. © 2011 by Quintessence Publishing Co Inc.
Keywords: Clinical evaluation; Dental implants; Overdenture